O uso da planta “pata–de–vaca” (Bauhinia Forficata) no tratamento do diabetes mellitus: um estudo na feira do Ver–o–Peso em Belém–Pará, Amazônia, Brasil - SILVA, Bruna Leticia Rosário da (Universidade Federal do Pará, 2023)
The Ver–o–Peso fair, located in Belém do Pará, is considered the largest open market in Latin America. There, a large number of plant species with varied medicinal properties are for sale, being used by residents of the city of Belém and metropolitan region for the treatment of numerous diseases. Despite this, many plants have not yet been scientifically identified/registered or patented by the pharmaceutical industry for their various uses and medicinal properties, which have been used, often for centuries, through traditional knowledge and ways. This work aims to characterize the forms of therapeutic/medicinal uses of the plant species known as “pata-de-vaca” (Bauhinia Forficata), in the treatment of Diabetes Mellitus, in the urban region of Belém do Pará, also verifying what they are. the active principles of this plant species that influence its effectiveness for the treatment of this disease. The research has a qualitative methodological approach, carried out through field research, using as data collection instruments, the application of free listing, interviews with key informants, application of forms/questionnaires, direct observation, audio recording of respondents and photographic records of the studied plant. The results of this research show that the urban region of the city of Belém do Pará has a large framework of traditional knowledge about medicinal plants and is very familiar with the practices employed in the use of medicinal plants that are used for health care. With that, the conclusion of this work, which in this case the research focus was the Bauhinia Forficata, showed that this plant has great commercialization and revealed efficacy when used for the treatment of Diabetes Mellitus. The findings also contributed to the recognition and appreciation of local knowledge and practices on the "pata-de-vaca" (Bauhinia Forficata) that are present in the urban region, and are being applied/used for treatment and consequent promotion of quality of life of diabetic patients.